2019
DOI: 10.1111/bjh.16361
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of paediatric acute myeloid leukaemia

Abstract: a schematic of the associate proteins interacting with core components RING1A/B and PCGF1-6 to form non-canonical PRC1 complexes. (B) PRC2 core subunits and the associate proteins required to form PRC2.1 and PRC2.2 complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Knocking out the BMI1 gene inhibits the cloning and sphere formation ability of CSCs ( 105 ). Studies have shown that abnormal levels of the histone demethylases lysine demethylase 6A (KDM6A) and KDM6B are associated with pediatric acute myeloid leukemia (AML) ( 106 ). Moreover, modification of histone proteins (H3K9ac, H3K27ac, H4K16ac, etc. )…”
Section: Ptm and Epigenetic Modification Regulate Cancer Stem Cellsmentioning
confidence: 99%
“…Knocking out the BMI1 gene inhibits the cloning and sphere formation ability of CSCs ( 105 ). Studies have shown that abnormal levels of the histone demethylases lysine demethylase 6A (KDM6A) and KDM6B are associated with pediatric acute myeloid leukemia (AML) ( 106 ). Moreover, modification of histone proteins (H3K9ac, H3K27ac, H4K16ac, etc. )…”
Section: Ptm and Epigenetic Modification Regulate Cancer Stem Cellsmentioning
confidence: 99%
“…Multiple epigenetic modifications regulate the transition from hematopoietic stem cells to lineage differentiation and maturation at the transcription level, including DNA methylation, histone modifications, and non-coding RNAs. Epigenetic dysfunction is common in most cancers, and extensive studies have also focused on the mechanisms of epigenetic dysregulation in AML, though AML has few mutations compared to other cancer types ( 5 , 8 ). The current advances of epigenetic modifications in AML are briefly summarized below ( Table 1 ).…”
Section: Epigenetic Regulation and Dysregulation In Adult And Pediatr...mentioning
confidence: 99%
“…Studies have shown that abnormal expression of histone codes is an important feature of cancer tissues and is related to the heterogeneity of cancer cells ( 31 , 32 ). Studies have shown that abnormal levels of the histone demethylases, KDM6A and KDM6B, are associated with pediatric acute myeloid leukemia (AML) ( 33 ). Moreover, modification of the histone proteins H3K9ac, H3K27ac, and H4K16ac plays an important role in the progression and prognosis of head and neck squamous cell carcinoma (HNSCC) ( 34 ).…”
Section: Research Hotspots Of Cancer Epigeneticsmentioning
confidence: 99%